Proceedings of the 9th International Workshop on Automation of Software Test 2014
DOI: 10.1145/2593501.2593502
|View full text |Cite
|
Sign up to set email alerts
|

Attack pattern-based combinatorial testing

Abstract: The number of potential security threats rises with the increasing number of web applications, which cause tremendous financial and existential implications for developers and users as well. The biggest challenge for security testing is to specify and implement ways in order to detect potential vulnerabilities of the developed system in a never ending quest against new security threats but also to cover already known ones so that a program is suited against typical attack vectors. For these purposes many appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
0
27
0
3
Order By: Relevance
“…Furthermore, the paper includes a detailed case study for testing various SUTs against our automated testing method and a detailed evaluation and comparison of the two sets of test suites is presented. We also draw useful conclusions that indicate that combinatorial testing is an efficient approach for security testing, building on the comparison of the test results of the testing methods given in [4], [8], [5]. Most important we present an extensive analysis in terms of (total) vulnerabilities found by our generated test suites using the combinatorial coverage measurement (CCM) tool [9], where it is revealed that the indicated security leaks are mainly caused by the interaction of few parameters.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the paper includes a detailed case study for testing various SUTs against our automated testing method and a detailed evaluation and comparison of the two sets of test suites is presented. We also draw useful conclusions that indicate that combinatorial testing is an efficient approach for security testing, building on the comparison of the test results of the testing methods given in [4], [8], [5]. Most important we present an extensive analysis in terms of (total) vulnerabilities found by our generated test suites using the combinatorial coverage measurement (CCM) tool [9], where it is revealed that the indicated security leaks are mainly caused by the interaction of few parameters.…”
mentioning
confidence: 89%
“…Finally, combinatorial testing has recently been employed as a method to model XSS attack vectors in [4], [8]. In detail, in [4] a novel combinatorial testing technique for generation of XSS attack vectors was first defined while in [8] the applicability of the previous technique has been further demonstrated by relaxing constraints and modelling white spaces in the attack grammar.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Bozic et al [28] proposed attack pattern-based combinatorial testing for detecting XSS vulnerabilities in web applications. In order to increase the coverage of our attack patterns, we applied the concept of combinatorial testing, as mentioned in Section III.…”
Section: Related Workmentioning
confidence: 99%